How “Anti-Union” Laws Saved Canadian Labour: Certification and Striker Replacements in Post-War Industrial Relations - Logan, John (Relations industrielles / Industrial Relations, 2002)
SummaryThis article analyzes the development in Canada of two critical differences between Canadian and U.S. labour policy: union recognition and state regulation of striker replacements. The development of public policy on these issues helps illuminate the fundamental principles of state intervention in post-war labour-management relations. Canadian lawmakers have circumscribed the economic weapons of unions and established stringent certification requirements; but they have also restricted employers’ recruitment of striker replacements and limited management involvement in the certification process. In the post-war decades, unionists attacked the “excessive intrusiveness” of Canadian labour policy and preferred the less intrusive system of state intervention in the U.S. Since the 1970s, however, Canada’s extensive regulation of labour relations has protected workers against market-driven anti-unionism and helped preserve the institutions of collective bargaining.